Effects of curing methods of concrete after steam curing on mechanical strength and permeability. (30th September 2020) - Liu, Baoju; Jiang, Junyi; Shen, Shuai; Zhou, Feng; Shi, Jinyan; He, Zhihai
Highlights: The subsequent curing regimes has great influence on the mechanical properties and permeability of steam-cured concrete. Surface permeability can be used to characterize the long-term performance of steam-cured concrete. Adequate subsequent curing will have a positive impact on macro-performance and microstructure of steam-cured concrete. Abstract: The accelerated hardening of concrete caused by steam curing has adverse effects on the microstructure and properties of concrete, so it is necessary to adopt appropriate curing method to reduce the damage caused by steam curing. The effects of curing methods on the properties of concrete after steam curing are worth studying. The compressive strength, non-evaporable water content and permeability (air, water and ion) of steam-cured concrete were tested under different subsequent curing conditions. Meanwhile, the internal microstructure was also investigated by image processing and SEM. The results show that the compressive strength of steam-cured concrete with four curing methods increases with the curing time, but the growth rates are different. The permeability of the concretes cured in the air decreased first and then increased with the curing time, while other curing methods decreased with curing time. The microstructure also shows that adequate subsequent wet curing can effectively reduce the adverse effects of steam curing on concrete.